Comparison of Start Codon Targeted (SCoT) and EST-SSR markers in sesame: Comparison of Start Codon Targeted (SCoT) and EST-SSR markers in sesame - MAINI BHATTACHARJEE; TAPASH DASGUPTA (Journal of Oilseeds Research, 2020)
Expressed sequence tag (EST)-SSR markers and Start codon targeted (SCoT) markers were compared to estimate genetic diversity among thirty sesame genotypes. To achieve this goal, the available sesame database was used as a resource for the development of novel microsatellite (SSR) and Start codon targeted (SCoT) markers. EST- SSR markers detected a mean of 4.34 alleles with a mean polymorphic information content (PIC) of 0.84, against SCoT markers with a mean of 9.6 alleles and a mean PIC of 0.79. SCoT markers amplified more null alleles than EST-SSRs. Geographical diversity did not corroborate with genotypic diversity as the cluster composition revealed that genotypes belonging to different geographical origin grouped in the same cluster.